Optic disc morphology may reveal timing of insult in children with periventricular leucomalacia and/or periventricular haemorrhage. Issue 11 (10th November 2003) - Jacobson, L; Hård, A-L; Svensson, E; Flodmark, O; Hellström, A
Abstract : Aims: To evaluate the relation between optic disc morphology and timing of periventricular white matter damage, defined as either periventricular leucomalacia (PVL) or periventricular haemorrhage (PVH), as estimated by neuroradiology. Methods: 35 children with periventricular white matter damage who had had neuroradiology performed and ocular fundus photographs taken had their photographs analysed by digital image analysis and compared with a control group of 100 healthy full term children. Timing of brain lesion was estimated by analysis of the brain lesion pattern on neuroradiological examinations (magnetic resonance imaging or computed tomography). Results: Four of 35 children had a small optic disc area; these four children had a brain lesion estimated to have occurred before 28 weeks of gestation. Nine of 11 children with a large cup area had a PVL/PVH estimated to have occurred after 28 weeks of gestation. The children with PVL/PVH had a significantly larger cup area (median 0.75 mm 2 ) than the control group (median 0.33 mm 2 ) (p = 0.001) and a significantly smaller neuroretinal rim area (median 1.58 mm 2 ) than the controls (median 2.07 mm 2 ) (p = 0.001). Conclusion: In a child with PVL/PVH and abnormal optic disc morphology, the possibilities of timing of the lesion should be considered.